The Effect of Games Strategy and Students Anxiety Toward the Students Listening Ability at The Second Year Students of SMA - M. Syauli Perdana Putra (International Journal of Educational Dynamics, 2019)
The research was conducted to explain the effect of Games Strategy and students anxieity on students listening ability. The design of this research was quasi experimental with 2x2 factorial design. The population of this research was the second year students of SMAN 1Tanjung Pinang, 2016/2017 academic year. Listening ability test and anxiety questionnaire were used as the research instruments. Then, the data were analyzed by using t-test formula and two ways Anova. The result of this research shows that (1) Games Strategy gave significant higher result in studens listening ability than Note Taking Strategy. It was indicated by the result of t-test which showed that tobserved (3,028) was bigger than ttable, (1,993), (2) Games Strategy gave significantly higher result inlistening ability of students with high anxiety than Note Taking Strategy. It was indicated by the result of t-test which showed that tobserved (3,338) was bigger than ttable (2,100), (3) Games Strategy did not give significantly higher result instudents listening ability with low anxiety than Note Taking Strategy.It was indicated by the result of t-test which showed that tobserved (0,569) was less than ttable (2,100), (4) There was no interaction between both strategies and students anxiety toward students listening aability, where Fobserved (2.809) was less than Ftable (3.25). In conclusion, Games Strategy gave significant higher result on students listenign ability than Note Taking Strategy and there was no interaction between teaching strategies and students anxiety toward students listening ability.